2022
DOI: 10.3390/app12105136
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Analysis of Deformation Refinement Characteristics of a Loess Tunnel Based on 3D Laser Scanning Technology

Abstract: Loess tunnels often undergo large-scale deformation with complex spatial and temporal distribution. Mastering the characteristics of spatial and temporal deformation is conducive to precise policy implementation and the control of large deformation of the tunnel. In this study, relying on the Yulinzi Tunnel in Gansu Province, China, based on 3D laser scanning technology, the tunnel was monitored for a short period of 24 h and a long period of 36 days. The refined characteristics of the temporal and spatial def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The results indicated that blasting must be performed at the appropriate moment to ensure the security of the structures. Y. Wu, Z. Zhou, S. Shao, Z. Zhao, K. Hu, and S. Wang [17] used 3D laser scanning technology to monitor the large deformation law of the loess tunnel based on the Yulinzi Tunnel and their results provided a reference for loess tunnel deformation control. Q. Huang, S. Liu, Y. Lv, D. Ji, and P. Li [18] applied a modified routine method and beam-spring model to their project based on a shield tunnel in Changsha.…”
Section: Research On Deep Rock Mass Engineeringmentioning
confidence: 99%
“…The results indicated that blasting must be performed at the appropriate moment to ensure the security of the structures. Y. Wu, Z. Zhou, S. Shao, Z. Zhao, K. Hu, and S. Wang [17] used 3D laser scanning technology to monitor the large deformation law of the loess tunnel based on the Yulinzi Tunnel and their results provided a reference for loess tunnel deformation control. Q. Huang, S. Liu, Y. Lv, D. Ji, and P. Li [18] applied a modified routine method and beam-spring model to their project based on a shield tunnel in Changsha.…”
Section: Research On Deep Rock Mass Engineeringmentioning
confidence: 99%
“…Many scholars have made significant contributions to the research conducted on 3D laser scanning. Wu et al [ 25 ] conducted long- and short-term monitoring of tunnels using 3D laser scanning technology. The temporal and spatial thinning characteristics of deformation at the representative points of the middle section, the working face of the roadway, and the mileage of the tunnel were analyzed during three-step and seven-step excavation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of geographical digital twin technologies, intelligent construction has gradually become an essential direction for tunnel excavation [6,7]. By constructing a digital twin geographical scene of tunnel excavation and establishing a dynamic connection between the physical world and the information world, it is possible to accurately control changes in tunnel excavation, which can alleviate or even eliminate the problem of over-and under-excavation during the construction process [8,9]; however, current geographical twin models in tunnel engineering primarily focus on modeling and visual description, and there are few studies in which digital twin ideas are integrated into deformation diagnosis during construction [10][11][12]. The lack of diagnostic analysis functions has become a significant obstacle to achieving intelligent construction and precise management of tunnel projects.…”
Section: Introductionmentioning
confidence: 99%